Effects of Cymbopogon winterianus Jowitt ex Bor essential oil on the growth and morphogenesis of Trichophyton mentagrophytes - Fillipe de Oliveira Pereira; Paulo Alves Wanderley; Fernando Antônio Cavalcanti Viana; Rita Baltazar de Lima; Frederico Barbosa de Sousa; Sócrates Golzio dos Santos; Edeltrudes de Oliveira Lima (Universidade de São Paulo, 2011)
Trichophyton mentagrophytes is a fungus causative agent of dermatophytosis, affecting humans worldwide. This has driven the search for products for the treatment of these infections. Accordingly, the aim of this study was to investigate the antifungal activity of the Cymbopogon winterianus essential oil against T. mentagrophytes. The antifungal tests consisted of antifungal screening, determination of MIC and MFC, analysis of the essential oil's effects on mycelial growth, germination of fungal spores, fungal viability, morphogenesis, cell wall (test with sorbitol) and cell membrane (cell leakage test) of T. mentagrophytes. Upon screening, the oil inhibited all strains, with zones of growth inhibition of 24-28 mm in diameter. The MIC was 312 μg/mL and CFM was 2500 μg/mL for almost all the strains tested. There were morphological changes in the conidia group, form and pigmentation of hyphae. The antifungal action of the product does not involve the cell wall and its action may involve the fungal plasma membrane. It is concluded that C. winterianus essential oil constitutes a potential antifungal product, especially for the treatment of dermatophytosis. Trichophyton mentagrophytes é um fungo causador de dermatofitoses, afetando humanos em todo o mundo. Isto direciona a busca de produtos para o tratamento destas infecções. Assim, este estudo teve por objetivo investigar a atividade antifúngica do óleo essencial de Cymbopogon winterianus contra T. mentagrophytes. Os ensaios antifúngicos foram constituídos do screening antifúngico, da determinação CIM e CFM, da análise dos efeitos do óleo essencial no crescimento micelial, na germinação dos esporos, na viabilidade fúngica, na morfogênese, na parede celular (ensaio com sorbitol) e na membrana celular (ensaio de lise celular) de T. mentagrophytes. No screening, o óleo inibiu todas as cepas, com zonas de inibição de crescimento de 24-28 mm de diâmetro. A CIM foi de 312 μg/mL e a CFM foi de 2500 μg/mL para quase todas as cepas testadas. O óleo essencial inibiu o desenvolvimento micelial, a germinação dos esporos e a viabilidade fúngica. Houve alterações morfológicas no agrupamento dos conídios, na forma e pigmentação das hifas. A ação antifúngica do produto não envolve a parede celular e parece estar envolvida com a membrana celular fúngica. Pode-se concluir que o óleo essencial de C. winterianus se apresenta como um potencial produto antifúngico, especialmente para o tratamento das dermatofitoses.